2013
DOI: 10.1517/17425247.2013.808186
|View full text |Cite
|
Sign up to set email alerts
|

Preference, satisfaction and errors with two dry powder inhalers in patients with COPD

Abstract: After 2 weeks' practice, patients preferred and were more willing to continue using Genuair than HandiHaler. Genuair was associated with higher patient satisfaction and fewer critical errors than HandiHaler.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 14 publications
0
53
0
4
Order By: Relevance
“…Patients using the Genuair devices required significantly less instruction, and retained that knowledge better after two weeks (significantly higher correct operation rate and fewer errors). A previous study found that significantly fewer patients experienced a critical error, defined as an error affecting drug delivery, with the Genuair device compared to the HandiHaler device (2.9% vs 19%, respectively, p\0.0001) [8]. These results suggest that the Genuair device is generally well tolerated in patients with COPD, and there were fewer errors affecting drug delivery than in both tiotropium devices.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Patients using the Genuair devices required significantly less instruction, and retained that knowledge better after two weeks (significantly higher correct operation rate and fewer errors). A previous study found that significantly fewer patients experienced a critical error, defined as an error affecting drug delivery, with the Genuair device compared to the HandiHaler device (2.9% vs 19%, respectively, p\0.0001) [8]. These results suggest that the Genuair device is generally well tolerated in patients with COPD, and there were fewer errors affecting drug delivery than in both tiotropium devices.…”
Section: Discussionmentioning
confidence: 63%
“…A previous study found that the preference rate was 45.6% for Respimat and 17.5% for HandiHaler, or in other words, Respimat was approximately 2.6 times more preferable than HandiHaler [13]. Another study found that the preference was 65.1% for Genuair and 16.6% for HandiHaler [8]. Since Respimat was 2.6 times more preferable than HandiHaler, the preference for Respimat was estimated to be 43% (16.6% 9 2.6).…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, the causes of patients' incorrect inhalation procedures and the determinants of patients' preference and acceptance had been extensively investigated, mainly being the patient's confidence and beliefs highly valued and regarded as the very crucial steps of the process to improve [9,15].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the determinants of patients' incorrect inhalation procedures [7,8] and those of patients' preference, acceptance, and satisfaction focused the attention of the majority of researchers [9][10][11][12][13][14][15]. The primary role of patients' viewpoint was then highly valued in recent years, even if the attempts to quantify objectively the correspondence between patients' beliefs and real usability in real life by means of specific instruments were only episodically pursued [11,[16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%